Tro og beslutsomhed - Albinus, Lars (Dansk Teologisk Tidsskrift, 2018)
Kierkegaard and Heidegger agree in seeing the prominence of human existence in the reflexive concern for itself and the anxiety which follows from recognizing the abyss of possibility and nothingness. However, Heidegger misses a notion of the formal structure of being in Kierkegaard’s work, which he conceives to merely offer a theological solution to questions that only a phenomenological outlook might provide on neutral grounds. Kierkegaard, on the other hand, lends his voice to forms of existence by which the “existentiell” dimension rests on the awakening of the Spirit as the condition of possibility. Contrary to Heidegger, Kierkegaard does not regard the fulfi llment of existence as something the subject can decide for itself without falling into despair. Using the literary figure of Hans Castorp from the novel Zauberberg by Thomas Mann, the article aims to show how easily the decision to confront life with love falls back into a spell of escapism, leaving Kierkegaard with the upper hand in pointing out the inadequacy of the human spirit, including philosophical endeavors, to ground itself.